Dyspnoea, disability, and distance walked: comparison of estimates of exercise performance in respiratory disease. Issue 6132 (22nd July 1978) - McGavin, C R; Artvinli, M; Naoe, H; McHardy, G J
Abstract : Forty-four patients with airway obstruction and 18 with pulmonary infiltration were studied in an attempt to correlate exercise tolerance, as assessed by a simple walking test, with basic respiratory function values and differing subjective assessments of exercise performance. The distance walked in 12 minutes was significantly correlated with the response to a structured questionnaire and with the patients' assessment of performance using an oxygen-cost diagram. The distance walked did not agree well with simple subjective estimates obtained in the clinical history. It was better correlated with forced vital capacity than with forced expiratory volume in one second in both groups of patients, and was well correlated with carbon monoxide transfer factor in those with pulmonary infiltration. The scatter of results, however, was such that exercise performance could not usefully be predicted from the respiratory function values or from subjective assessments. Simple exercise tests are an essential part of assessing disability and response to treatment in patients with respiratory impairment.